PEMBERDAYAAN KELOMPOK SUAMI SIAGA PADA PERILAKU PERAWATAN KEHAMILAN (ANC) UNTUK PENCEGAHAN KOMPLIKASI KEHAMILAN USIA DINI DI WILAYAH PUSKESMAS BUKIT RAWI - Legawati, Legawati; Natalina, Riny (LPPM Institut Pendidikan Nusantara Global, 2024)
Teenage pregnancy (early age) is one of the important problems in the 21st century. There are more than 16 million children in the world born to mothers aged 15-19 years. Indonesia is one of the regions with the highest presentation of early marriage in the world with a rank of 37 and the second highest in ASEAN. Central Kalimantan Province is ranked second in early pregnancy, with an increasing incidence of pregnancy complications based on data reported by one of the Referral Hospitals in Central Kalimantan Province. The evaluation was carried out using questionnaires on knowledge in the prevention of pregnancy complications. There was an increase in husbands' knowledge after empowerment, before empowerment was carried out there were 2 people (10%) in the good category, 12 people (60%) in the sufficient category and there were 8 people (30%) who were included in the less category. After the formation of the standby husband group, there was an increase in knowledge in the good category of 17 people (85%), in the sufficient category of 2 people (10%) and in the category of less than 1 person (5%). Husband empowerment can increase husband's knowledge in early detection of pregnancy complications. The establishment of an early pregnancy pregnancy alert group requires monitoring and supervision from the Puskesmas Bukit Rawi.